Model Pengendalian Internal Pesantren - Abd. Mujib; Siti Maria Wardayati; Muhammad Miqdad (Jurnal Akuntansi dan Pajak, 2021)
This research aims to produce a model of internal control at Pesantren as an educational institution that upholds the values of Islamic culture and traditions. In managing its organization, each entity has the same potential to correct fraud. One of supports expected to be able to prevent fraud and become an effective means to achieve goals is the internal control. The qualitative researchis conducted with a strategy grounded theory at Pondok Pesantren Salafiyah Syafi’iyah Sukorejo. The results of this study found that the unique element of Pesantren is the value of spirituality that underlies all activities. These elements of spirituality are categorized as the following, namely 1) the categories of beliefs and attitudes consisting of iman, akhlak, amanah, spiritual connection and barokah, 2) practice consisting of niat, khidmah, musyawarah and istikharah, 3) management consisting of Pengasuh Pesantren, centralization and salaf-khalaf, and 4) pesantren heritage consisting of ibadah, wirid, hizib and istiqamah. These spiritual elements become effective fortress for pesantren in carrying out all its activities, and are named Spiritual-based Internal Control